2022
DOI: 10.1617/s11527-022-01995-9
|View full text |Cite
|
Sign up to set email alerts
|

Grain angle determination of silver birch by laser light scattering and tensile fracturing

Abstract: Reliable non-destructive methods for grain angle determination are essential for the evaluation of mechanical properties of timber. In the present study, the detection of grain angle by means of laser light scattering patterns is investigated on small-scale specimens and timber boards of silver birch, along with the relationship to fracture angle and tensile strength. Results on small-scale specimens indicate applicability of laser scattering method, as the detected grain angles and the fracture angles show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…A total of 119 specimens were investigated. The specimens were sawn from the ends of timber boards with a wide range of grain angles [5]. The specimens are (dogbone) shaped with a reduced gauge region of 200 mm in length (Figure 1).…”
Section: Experimental Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 119 specimens were investigated. The specimens were sawn from the ends of timber boards with a wide range of grain angles [5]. The specimens are (dogbone) shaped with a reduced gauge region of 200 mm in length (Figure 1).…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…Density was measured from a section of the gauge region after testing and the influence of density on the tension strength of this sample was investigated in a previous study [5]. Wherein, it was found that density had no unambiguous relationship with the tension strength.…”
Section: Experimental Investigationsmentioning
confidence: 99%